Month-to-Month Variability of Autumn Sea Ice in the Barents and Kara Seas and Its Relationship to Winter Air Temperature in China - Chuhan Lu; Kaili Li; Shaoqing Xie; Zhaomin Wang; Yujing Qin (Advances in Meteorology)
The variation of autumn Arctic sea ice is a critical indicator of temperature anomalies over the Eurasian continent during winter. The retreat of autumn Arctic sea ice is typically accompanied by negative anomalous winter temperatures over the Eurasian and North American continents. However, such sea ice temperature linkages notably change from month to month. The variation of the autumn Arctic sea ice area and the relationship between the month-to-month sea ice and winter temperature anomalies in China are investigated using the Hadley Centre’s sea ice dataset (HadiSST) and the European Centre for Medium-Range Weather Forecasts (ECMWF) reanalysis dataset (ERA-Interim) during 1979–2018. We present the following results: The sea ice in the Barents and Kara seas (BK) during the autumn and winter seasons shows notable low-frequency variability. The retreat of sea ice in the BK from September to November is significantly associated with negative temperature anomalies in the following winter in China. However, the linkage between the sea ice in the BK in September and the winter temperatures is stronger than that in both October and November. An anomalous positive surface pressure is exhibited over the northwestern part of Eurasia in the winter that is linked to decreasing sea ice in the BK in the preceding September. This surface pressure favors the persistence and intensification of synoptic perturbations, such as blocking highs and surface cold highs, as well as the intensification of the Siberian High and the East Asian winter monsoon. These favorable conditions ultimately contribute to the formation of large-scale winter cold anomalies in China. Compared to low sea ice cover in October and November, a more oceanic heat storage in the upper BK induced by low sea ice cover in the BK leads to a larger heat release to tropospheric atmosphere in winter by surface heat flux and upward longwave radiation in the BK. This regional tropospheric warming results in a higher barotropic positive height anomaly over the Ural Mountains, and then more active cold advection from the high latitude affects East Asia.